Peranan Orang Tua terhadap Akhlak Anak dalam Perspektif Pendidikan Islam - Eny Fatimatuszuhro Pahlawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This study aims to examine the role of parents in child morals in the perspective of Islamic education. This type of research is qualitative through library research, the source of data from the literature in the form of books, written works, and other written sources contained in print and electronic media, which are related to the subject matter of the discussion. The data analysis technique used is a descriptive qualitative analysis technique. The results showed that in the perspective of Islamic education, parents have a large role in the formation of children's morals. This illustrates that in a family that is used as a role model for their children are parents.